This was not our war : Bosnian women reclaiming the peace - Hunt, Swanee (E-Duke books scholarly collection., 2004)
Combines Bosnian women's personal testimony about the recent war and its aftermath with Ambassador Hunt's analysis of the U.S. government's appproach to the conflict.